2014
DOI: 10.1177/1099800414532709
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Muscle-Related Cytokines and Selected Patient Outcomes in the ICU

Abstract: Introduction Systemic cytokines produced by contracting skeletal muscles may affect the onset and severity of intensive care unit (ICU)-acquired weakness after critical illness. Aims The purpose of this research was to determine the serum levels of interleukin (IL)-8, IL-15, and tumor necrosis factor-α (TNF-α) among patients receiving mechanical ventilation for >48 hr and examine the relationships of these myokines to outcomes of patient delirium, muscle strength, activities of daily living (ADLs), duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…A previous study has reported that systemic inflammation was associated with ICU-acquired weakness and indicated that IL-6, TNF-α, or other cytokines could play roles in this pathogenesis [26]. In our study, one patient with ICU-acquired weakness did not show any improvement during treatment with PMMA-CHD.…”
Section: Discussioncontrasting
confidence: 48%
“…A previous study has reported that systemic inflammation was associated with ICU-acquired weakness and indicated that IL-6, TNF-α, or other cytokines could play roles in this pathogenesis [26]. In our study, one patient with ICU-acquired weakness did not show any improvement during treatment with PMMA-CHD.…”
Section: Discussioncontrasting
confidence: 48%
“…Rats treated with recombinant TNF or IL-1β showed a significant reduction in total muscle protein content and a reduced expression of myofibrillar proteins [ 201 , 202 ]. ICU patients displayed increased TNF serum levels [ 203 ], and maximal TNF plasma levels were found to be higher in patients who developed ICUAW as compared with control subjects [ 204 ]. Importantly, the administration of an anti-TNF antibody inhibited the sepsis-induced increase in muscle proteolysis in rats, indicating that TNF is an important regulator of muscle protein breakdown during sepsis [ 205 ].…”
Section: Role Of Proinflammatory Cytokines In Inflammation-induced Muscle Wastingmentioning
confidence: 99%
“…We estimated that a sample size of 50 would have .80 power to detect a .30 effect size with an a of .10, using Analysis of Covariance (ANCOVA) repeated measures both within and between interactions (Faul et al, 2007). The effect size used in this calculation was larger than what we had obtained in an earlier study (Winkelman, Johnson, & Gordon, 2015); we anticipated fewer missed interventions and greater dose from twice-daily completion leading to a greater effect. We selected a larger a value due to the established safety of the intervention (Morris et al, 2008;Winkelman et al, 2012).…”
Section: Sample Sizementioning
confidence: 94%